Pengaruh Variasi Molaritas dan Jenis Inhibitor terhadap Ketahanan Korosi dan Morfologi Baja Tulangan Beton - Afira Ainur Rosidah; Vuri Ayu Setyowati; Nasrul Amin (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2022)
Concrete reinforcement steel is often needed as a reinforcement for a building. It is like other materials; steel concrete will experience a weakening of quality due to the corrosion process. These steels are commonly coated using inhibitors to slow down the corrosion rate. In this research, three types of inhibitors, namely sodium nitrite, phosphoric acid, and carboxylic acid will be mixed into the corrosive medium of HCl and aquades. Dissolution of each inhibitor against corrosive media uses three different molarities, that are 0.2 M, 0.5 M, and 0.8 M. Each inhibitor solution and the corrosive medium will be used as an immersion medium to carry out the corrosion process of reinforced concrete steel. For the evaluation process, each of these specimens will be calculated the value of the corrosion rate and the efficiency of the inhibitor; as well as morphological analysis will also be carried out to determine how the impact of corrosion on the reinforced concrete steel. The results of this study stated that a carboxylic acid inhibitor with a concentration of 0.8 M; its combination led at the best performance with the inhibitor efficiency of 30.20%, while a phosphoric acid inhibitor with a concentration of 0.2 M had the worst performance with an inhibitor efficiency of 24.83%. In addition, from the morphological analysis, it was also found that giving a higher concentration of an inhibitor can reduce the corrosion rate.Keywords: reinforcing steel, inhibitor, molarity, corrosion rate